Effects of Hypericum scabrum extract on learning and memory and oxidant/antioxidant status in rats fed a long-term high-fat diet - Ganji, Ahmad; Salehi, Iraj; Nazari, Masoumeh; Taheri, Masoumeh; Komaki, Alireza (Metabolic brain disease, 2017)
A high-fat diet (HFD) causes deficits in learning and memory by increasing oxidative stress. Antioxidants are known to improve learning and memory. Since Hypericum scabrum (H. scabrum) extract is rich in antioxidants, the aim of this study was to investigate the effects of the administration of H. scabrum extract on passive avoidance learning (PAL), novel object recognition (NOR), and locomotor activity in male rats on a HFD. Fifty-four male Wistar rats (weighing 220 ± 10 g) were divided into the following six groups: (1) Control (standard diet), (2) Ext100 (standard diet supplemented with 100 mg/kg extract once/day), (3) Ext300 (standard diet supplemented with 300 mg/kg extract once/day), (4) HFD (high-fat diet), (5) HFD + Ext100, and (6) HFD + Ext300. Rats in these groups were maintained on their respective diets for 3 months. In the PAL test, the step-through latencies in the retention test (STLr) were significantly higher in the HFD + extract group than in the HFD group. The time spent in the dark compartment (TDC) was significantly lesser and the time spent in exploring the novel object was significantly greater in the HFD + extract group than in the HFD group. In the HFD-fed rats, the activity of catalase had significantly decreased, and level of malondialdehyde had significantly increased; H. scabrum extract administration significantly reversed these changes. In conclusion, these results suggested that the administration of H. scabrum extract and its strong antioxidant properties enhanced learning and memory and reversed the memory impairment induced by chronic HFD consumption.